Italian consensus statement (2020) on return to play after lower limb muscle injury in football (soccer). Issue 1 (15th October 2019) - Bisciotti, Gian Nicola; Volpi, Piero; Alberti, Giampietro; Aprato, Alessandro; Artina, Matteo; Auci, Alessio; Bait, Corrado; Belli, Andrea; Bellistri, Giuseppe; Bettinsoli, Pierfrancesco; Bisciotti, Alessandro; Bisciotti, Andrea; et al.
Abstract : Return to play (RTP) decisions in football are currently based on expert opinion. No consensus guideline has been published to demonstrate an evidence-based decision-making process in football (soccer). Our aim was to provide a framework for evidence-based decision-making in RTP following lower limb muscle injuries sustained in football. A 1-day consensus meeting was held in Milan, on 31 August 2018, involving 66 national and international experts from various academic backgrounds. A narrative review of the current evidence for RTP decision-making in football was provided to delegates. Assembled experts came to a consensus on the best practice for managing RTP following lower limb muscle injuries via the Delphi process. Consensus was reached on (1) the definitions of 'return to training' and 'return to play' in football. We agreed on 'return to training' and RTP in football, the appropriate use of clinical and imaging assessments, and laboratory and field tests for return to training following lower limb muscle injury, and identified objective criteria for RTP based on global positioning system technology. Level of evidence IV, grade of recommendation D.